Attityd till cancelkultur: En kvalitativ undersökning på personlighetsdrag och sociala processer - Ronkainen,Thea; Fransson,Emma (2025)
The aim of this study is to examine how young adults in Sweden describe their experiences and relate to the phenomenon cancel culture, as well as to identify patterns between 1) internal psychological factors and 2) social factors in relation to their attitudes towards cancel culture. The research question is: How do young Swedish adults express their attitudes toward cancel culture? Based on the Big Five theory and theories on social influence and parasocial relationships, semi-structured interviews were conducted with eight participants, along with the personality test NeoNeutral 40 1.2. The analysis was carried out using Interpretative Phenomenological Analysis, and three thematic clusters were identified: 1) when emotion meets opinion, 2) speaking freely and acting wisely and 3) a critical stance. The results show patterns between attitudes toward cancel culture and the personality traits of openness and conscientiousness, social pressure and emotional bonds to public figures. The study highlights how engagement in or rejection of cancel culture may be influenced by both the respondents personality traits as well as social norms. These findings contribute to an enriched understanding of a current digital phenomenon and may be relevant in the fields of media psychology, crisis management and future research in personality and social psychology.
Keywords: Cancelkultur; personlighet; social påverkan; parasociala relationer; tolkningsfenomenologisk analys; Cancel culture; personality; social influence; parasocial relations; Interpretative Phenomenological Analysis